Pengharapan di Masa Sulit dalam Perspektif Antropologi Kristiani - Franciscus Hardjosetiko (Seri Filsafat Teologi, 2021)
Man is created by God according in His own image. He has made and crowned him with glory and honour. It can be seen in man’s nature that, as long as he lives in this mortal world, he is equipped with awareness, intelligence and conscience. This is so important because the goal of man’s life is the eternal life, united with God. This must be the hope for every believer, although life in this world is not easy. Man is often hit by hard times. Hope, however, empowers man to optimally develop his awareness, intelligence and conscience.